The Elasticity Modulus Of High-Quality Concrete With Saturated Alwa and Fly Ash - Alfan Figo Ramadhan; Euis Kania Kurniawati; Nia Kartika (International Journal Labs, 2022)
Background: High-quality concrete requires a low water-cement factor, so it is necessary to add pozzolanic materials, one of which is fly ash. However, the use of pozzolanic material causes high shrinkage and causes the concrete to become moist during the hardening process so that the solution to reducing cracking is one of them by using the internal curing method, so it is necessary to have IC materials such as Always. Objective: aims to counteract the self-drying effect in low water-cement ratio mixtures. This internal curing treatment uses lightweight aggregate that is moistened to act as a reservoir that can release water as needed to keep the hydrating cement paste structure saturated. Methods: the internal curing method requires additional materials capable of providing additional water, one of which is ALWA (Artifical Light Weight Aggregate) which is capable of being an IC agent. Results: The results of this study obtained a high compressive strength (about 750 kg/cm2) using a cement content of 546 kg, w/c = 0.28, the addition of 10% silica fume and 1.5% superplasticizer.